Influencer credibility and homophily effects on Generation Z purchase intention of msme products: The mediating role of Instagram engagement - Balqis, Nabiila Alyaa; Yasri, Yasri (Universitas Negeri Padang, 2025)
This study investigates the impact of influencer credibility, influencer homophily, and influencer engagement on the purchase intention of Micro, Small, and Medium Enterprises (UMKM) products among Generation Z in Padang City, focusing on the Instagram platform. Utilizing a quantitative approach, data were collected from 180 respondents through structured questionnaires. The findings reveal that influencer credibility positively and significantly affects influencer engagement but does not directly influence purchase intention. In contrast, influencer homophily significantly enhances both influencer engagement and purchase intention. Additionally, influencer engagement positively influences purchase intention and mediates the relationship between both influencer credibility and influencer homophily on purchase intention.